Impact of accounting conservatism on IPO under-pricing: evidence from India - Nenavath Sreenu; Ashis Kumar Pradhan; Vo Xuan Vinh; B. Koteswara Rao Naik (Cogent Economics & Finance, 2022)
In this paper, we investigate whether the use of accounting conservatism in India decreases IPO underpricing, which is of attention to stakeholders and supervisors. Furthermore, the study examines how asymmetry information affects the implication of accounting conservatism for IPOs. Based on a regression analysis of 527 firms that went public through IPOs of "A" shares listed on the national stock exchanges between 2000 and 2020, the paper also examines whether the relationship between conservatism and under-pricing is robust to alternative measures of accounting conservatism, mean regressions, sample exclusions, and endogenous treatment models. The research study finds that accounting conservatism is negatively associated with the degree of IPO under-pricing, and the association between accounting conservatism and IPO under-pricing is more perceptible when information asymmetry is high. The paper's originality should shed light on what drives IPO underpricing and how it could be affected by accounting conservatism in an Indian economy, and provide find evidence that legal origin, a factor linked to the practice of conservatism, influences the relationship between under-pricing and conservatism.
Keywords: M40; M41; M42; M48; M49; 330; accounting conservatism; asymmetry information; IPO; under-pricing